Randomized Trial of Albendazole with Combination of Pyrantel Pamoate-Mebendazole in Treatment of Mixed Helminthiasis in Children - Tiangsa Sembiring; Evi Kamelia; T. Ernalisna; Syahril Pasaribu; Chairuddin P. Lubis (Paediatrica Indonesiana, 1999)
This study aimed to compare the effectiveness of albendazole and pyrantelpamoate-mabendazole combination for the treatment of mixed infection of soil transmitted helminthiasis. Subjects were students of primary school in Tanjung Anom village, North Sumatra. The study was performed from September until November 1995. Pat.ients were randomired into two groups; Group A received 400 mg oral albendazole in single dose while group B recieved a combination of pyrantel pamoate 10 mg/kg BW as a single dose and mebendazole 2 x 100 mg in three consecutive days.From 541 children examined, mixed soil transmitted helmlnthiasis was found in 374 children (69%). Analysis was performed on 182 children in Group A and 184 in Group B. Comparison between two group, cure rate at 3 weeks after treatment proved to the significantly different (p<0.05). We conclude that albendawle was more effective than combination of pyrantel pamoate- mebendawle for the treatment of mixed infection of soil transmitted helminthiasis. Administration more simple and have minimal side effect.